REFLEKSI NILAI SEGARA KERTHI DALAM GAME SEGARA WATCH SEBAGAI MEDIA EDUKASI - I Wayan Suwadnyana; Saskara, I Putu Adi; Bagus Nesa Sanjaya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The development of information and communication technology has opened the door to various educational innovations, and one of the innovations that stands out is the use of video games as an educational medium. In this context, the game